2013
DOI: 10.1055/s-0033-1338511
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Aroylguanidines by an Unexpected Demethylation-Addition Cascade

Abstract: A simple and efficient method was developed for the synthesis of N-aroyl-N′-arylguanidines under mild conditions by an unexpected demethylation-addition cascade reaction of readily available N-cyanoimidates with aryl amines. Moreover, 1-aryl-2-aminoquinazolin-4(1H)-ones and 2-(arylamino)quinazolin-4(3H)-ones can also be prepared by selective cyclization reactions of (2-fluorobenzoyl)-or (2-nitrobenzoyl)guanidines, respectively. This method provided two attractive strategies for the preparation 2-aminoquinazoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…(91 mg, 75%). Compound 5m is known and spectral data were in agreement with the proposed structure and matched those reported in the literature …”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…(91 mg, 75%). Compound 5m is known and spectral data were in agreement with the proposed structure and matched those reported in the literature …”
Section: Methodssupporting
confidence: 86%
“…Another approach is to prepare acylguanidines from N -cyanobenzamides, , which generally are prepared by reacting the corresponding acyl chloride and sodium cyanamide. They have also been prepared via radical reactions including the rearrangement reaction of acylcyanamides and diphenyldisulfide followed by subsequent reaction with amines and the synthesis of polycyclic acylguanidines via a radical cascade cyclization reaction . Notably, the synthesis of acylguanidines from cyanoimidates has been proposed to proceed via an N -cyanobenzamide intermediate stemming from amine-promoted demethylation of the cyanoimidate starting material . We and others have previously shown that N -cyanobenzamides can be prepared from readily available aryl halides and how these compounds can be utilized as valuable precursors in the synthesis of N -heterocycles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several synthetic methods are available for the preparation of quinazolinones and 2-aminoquinazolinones, , including fusion of anthranilic acid with amides, amidation of 2-aminobenzoic acids and its derivatives, , reaction of resin-bound isothioureas with isatoic anhydrides, and acylation of ortho -fluorobenzoic acids with substituted guanidines and subsequent ring closure . Furthermore, 1-aryl-2-aminoquinazolin-4-ones and 2-(arylamino)­quinazolin-4-ones have been obtained from the reaction of N -cyanoimidates and arylamines . However, these reactions are often performed under harsh reaction conditions and require multistep procedures or complex intermediates, and there is still a need for new and efficient methods to prepare this important ring system.…”
Section: Introductionmentioning
confidence: 99%